Effect of flame-made metal (M=Pt, Nb, Ru)-Loaded In2O3on NO2gas sensing - K. Inyawilert (2018)
Unloaded In 2 O 3 and M (M=Pt, Nb and Ru)-loaded In 2 O 3 nanoparticles loaded with 0.25-1.00wt% M were successfully synthesized in a single step by the flame spray pyrolysis (FSP) technique. Indium nitrate, platinum (II) acetylacetonate, niobium ethoxide and ruthenium (III) acetylacetonate were used as In, Pt, Nb and Ru precursors respectively, dissolved in ethanol. The unloaded In 2 O 3 and M-loaded In 2 O 3 nanoparticles were characterized. The average diameter of the spherical nanoparticles were in the range of 10.2 to 15.2 nm under 5/5 (precursor/oxygen) flame conditions. All peaks can be confirmed to correspond to the cubic structure of In 2 O 3 (JCPDS No. 03-065-3170). Gas sensing studies showed that Pt-loaded In 2 O 3 gave an enhancement in NO 2 sensing in term of response and selectivity. 0.5wt% Pt/In 2 O 3 exhibited good selectivity against H 2 S and NO gases. When compared to other metal loading such as Nb and Ru, Pt-loaded In 2 O 3 exhibited much better gas sensing against NO 2 , H 2 S and NO gases.